Radicalisation in Immigrant Youth: Differential Influence Analysis of Psychosocial Factors - Almudena Macías León; Francisco Cosano Rivas; Auxiliadora Durán Durán (RIMCIS, 2022)
The radicalisation of young immigrants in Europe is a phenomenon of scientific and political relevance. The study aimed to analyse the degree of consensus on the differential influence on the radicalisation process of various factors (attitudinal, contextual, historical and protective), primarily included in the VERA-2, related to multiple socio-demographic categories and the processes of radicalisation in opinion and action. Applying a Delphi analysis methodology, the results point to the difficulty of reaching a consensus on the differential influence of the factors that affect the radicalisation of young migrants according to the categories examined. This consensus is appropriate concerning the distinction between radicalisation in action and radicalisation in opinion, showing the multiplicity of influential factors, especially in the case of radicalisation in opinion. The importance of protective, contextual, and attitudinal factors is evident for this type of radicalisation, while for radicalisation in action, a high consensus is reached on historical and contextual factors. Interventions aimed at the attitudinal sphere, rejection and prevention of violence, active policies of social inclusion, and spaces for intercultural dialogue and community participation are proposed as lines of work to prevent the radicalisation of young immigrants.